2021
DOI: 10.3390/ijerph18031174
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 Pandemic on Psychiatric Admissions to a Large Swiss Emergency Department: An Observational Study

Abstract: The coronavirus disease 2019 (COVID-19) pandemic is a public health emergency with profound mental health consequences. The psychiatric emergency department (ED) plays a key role during this mental health crisis. This study aimed to investigate differences in admissions at a Swiss psychiatric ED from 1 April to 15 May during a “pandemic-free” period in 2016 and a “during-pandemic” period in 2020. The study included 579 consultations at psychiatric ED in the “during-pandemic” period and 702 in the “pandemic-fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
91
7
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(126 citation statements)
references
References 46 publications
23
91
7
5
Order By: Relevance
“…Over the period examined, there was a 30% reduction in HED psychiatric consultations in 2020 compared with 2019. This reduction in psychiatric consultations in the early stages of the pandemic is consistent with evidence from other countries (4)(5)(6)(7)(8)(9)(10)(11).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Over the period examined, there was a 30% reduction in HED psychiatric consultations in 2020 compared with 2019. This reduction in psychiatric consultations in the early stages of the pandemic is consistent with evidence from other countries (4)(5)(6)(7)(8)(9)(10)(11).…”
Section: Discussionsupporting
confidence: 88%
“…In general, projections indicate an increase in depression and post-traumatic stress disorder (PTSD) on a basis of biological mechanisms and social consequences (2,3). On the other hand, some preliminary reports on mental health management in the acute phase of the pandemic have found a decrease in requests for psychiatric consultations in hospital emergency departments (HEDs) (4)(5)(6)(7)(8)(9)(10)(11). Clearly, the type of organization of mental health care has a strong influence on how each country copes with the crisis.…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, it is shown for the first time in a large inpatient sample (total n = 64,502) that the proportion of urgent and involuntary admissions for all psychiatric diagnoses significantly increased in 2020 as compared to 2018 and 2019. This increase might have been caused by a focus on acute psychiatric care due to shifting of health care towards COVID-19 treatment ( Ambrosetti et al, 2021 ; Bojdani et al, 2020 ). Restrictions imposed by governments might have tightened admission criteria for less urgent admissions and led to a relative increase in the proportion of urgent and involuntary admissions even though psychiatric wards are a more independent department from the rest of the tertiary care system ( Fasshauer et al, 2021b ).…”
Section: Discussionmentioning
confidence: 99%
“…In Germany, the partial lockdown decreased number of emergency hospital admissions for psychiatric disorders ( Fasshauer et al, 2021a ). Some evidence exists that acute and involuntary admissions increased during the first lockdown ( Ambrosetti et al, 2021 ; Carpiniello et al, 2020 ; Itrat et al, 2020 ; Tromans et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the governments of each nation hypothesized the negative socio-economic impact of the pandemic with detrimental consequences on local and worldwide health services [1]. For this reason, most governments obliged the general population to several security measures, including quarantine, lockdown, and confinement [2,3].…”
Section: Introductionmentioning
confidence: 99%